Gamma-delta T lymphocytes and 25-hydroxy vitamin D levels as key factors in autoimmunity and inflammation: the case of zoledronic acid-induced acute phase reaction. (April 2015) - De Santis, M; Cavaciocchi, F; Ceribelli, A; Crotti, C; Generali, E; Fabbriciani, G; Selmi, C; Massarotti, M
Zoledronic acid (ZA) infusion for osteoporosis is frequently associated with the onset of an acute phase reaction (APR) secondary to the activation of γδ T cell receptor (TCR) lymphocytes (γδ T cells) and to low vitamin D levels, similar to what is observed in chronic inflammation and autoimmunity. In this study we investigated whether the phenotype of γδ T cells is associated with APR and 25-OH vitamin D (25-OHvD) levels. For flow-cytometry analysis, peripheral blood samples were obtained from 52 osteoporotic women prior to 5 mg ZA intravenous infusion and from nine women (five with APR) one week later. Twenty-six/52 (50%) patients reported APR and APR+ cases had a higher percentage of central memory Th1-like γδ T cells. One week after ZA infusion, APR was associated with a decreased percentage of central memory Th1-like γδ T cells, an increase in the percentage and activation of effector memory Th1-like γδ T cells, and an increase in Th17-like γδ T cells. Lower 25-OHvD levels were significantly associated with APR, but no correlation was found between 25-OHvD level and γδ T cell percentage or subsets. In conclusion, patients experiencing APR related to ZA infusion have lower 25-OHvD levels and we suggest that the higher percentage of central memory Th1-like γδ T cells and the expansion of effector memory Th1-like and Th17-like γδ T cells are associated with the occurrence of APR.